NMR methods for the fast recording of diffusion - Pages, Guilhem; Kuchel, Philip W. (Diffusion Fundamentals, 2007)
The time taken to complete an NMR diffusion experiment is typically 10 minutes. For systems that rapidly evolve conventional pulsed field gradient spin-echo (PGSE) experiments cannot be used to obtain reliable estimates of molecular mobility. Modern ‘fast-diffusion’ experiments provide a means of obtaining this information and thus open up new vistas for the application of PGSE NMR. In this paper we review the various advantages and disadvantages of these methods.